Exon2 of HIV-2 Tat contributes to transactivation of the HIV-2 LTR by increasing binding affinity to HIV-2 TAR RNA. - Rhim, H (1994)
Human immunodeficiency virus types 1 and 2 (HIV-1 and HIV-2) express related Tat proteins that are encoded in two exons. Tat proteins bind directly to the TAR RNA element contained in the 5' ends of viral transcripts and thereby stimulate transcription through an as yet unidentified mechanism. We have investigated the functional significance of exon2 of the HIV-2 Tat protein by examining properties of proteins consisting of exon1 alone or exon1 + 2. In transactivation assays in vivo, exon2 modestly increased HIV-2 Tat stimulation of transcription from the HIV-2 long terminal repeat (LTR) but had no effect on transcription from the HIV-1 LTR. In HeLa cells, exon2 increased transactivation of the HIV-2 LTR by approximately three-fold, while in COS and Jurkat cells this value was less than two-fold. In binding assays in vitro, exon2 increased the binding affinity of the HIV-2 Tat protein to HIV-2 TAR RNA. Results with GAL4 fusion proteins and a synthetic promoter containing GAL4 DNA binding sites indicated that exon2 does not contribute to the HIV-2 Tat activation domain. These observations suggest that exon2 of HIV-2 Tat contributes to transactivation of the HIV-2 LTR by increasing the binding affinity to HIV-2 TAR RNA.